PENGARUH PEMBERIAN JUS SEMANGKA TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS LUBUK BUAYA PADANG TAHUN 2017 - Rebbi Permata Sari; Ledia Restipa; Marsia Yonira Putri (JIK-JURNAL ILMU KESEHATAN, 2017)
The prevalence of hypertension increased from year to year. Puskesmas Lubuk Buaya had the highest occurrence of hypertension on the elderly with 3614 cases. One way that could be done to control hypertension was to control blood pressure by drinking watermelon juice. The objective of the study was to find out the effect of watermelon juice on the blood pressure decline of the elderly sufferring from Hypertension in the work area of Puskesmas Lubuk Buaya Padang in 2017.The type of the study was quasy-experimental with two-group pretest-posttest study design. The study was conducted in the work area of Puskesmas Lubuk Buaya Padang in 2017 from January to August. The data collecting was done in 18 days from July 3 to 20 2017.  The populations of the study were all the elderly sufferring from hypertension and visiting Puskesmas Lubuk Buaya Padang. The sampling technique used was accidental sampling with the number of samples of 30 people. The data were analyzed by univariate and bivariate analysis using Dependent T-test.The result of the study showed that the mean of systolic and diastolic blood pressure in pretest in the intervention group was 174,00/96,67 mmHg, and in the control group was 169,33/96,67 mmHg. The mean of systolic and diastolic blood pressure in posttest in the intervention group was 156,00/82,00 mmHg, and in the control group was 167,33/93,33 mmHg. From the result of the statistical test, it was found out that the p value was 0,000 (p  which meant that there was an effect of watermelon juice on the blood pressure decline of the elderly sufferring from Hypertension in the work area of Puskesmas Lubuk Buaya Padang in 2017.There was an effect of watermelon juice on blood pressure decline of people sufferring from Hypertension. It is suggested that nurses of Puskesmas Lubuk Buaya Padang socialize the benefits of watermelon to lower blood pressure for people with hypertension.Penelitian ini bertujuan untuk mengetahui pengaruh pemberian jus semangka terhadap penurunan tekanan darah pada lansia penderita hipertensi di wilayah kerja Puskesmas Lubuk Buaya Padang Tahun 2017Jenis penelitian ini adalah Quasy Eksperimen dengan rancangan penelitian Two Group Pretest-Postest Design. Penelitian ini dilakukan di wilayah kerja Puskesmas Lubuk Buaya Padang Tahun 2017 pada bulan Januari-Agustus, pengumpulan data dilakukan selama 18 hari pada tanggal 03-20 Juli 2017. Populasi dari penelitian ini adalah semua lansia penderita hipertensi yang berkunjung di Puskesmas Lubuk Buaya Padang. Penarikan sampel dilakukan secara accidental sampling dengan jumlah sampel sebanyak 30 orang. Analisa data secara univariat dan bivariat menggunakan uji T-Tes Dependent. Rerata tekanan darah sistolik dan diastolik pretest pada kelompok intervensi adalah 174,00/96,67 mmHg dan pada kelompok kontrol adalah 169,33/96,67 mmHg. Rerata tekanan darah sistolik dan diastolik posttest pada kelompok intervensi adalah 156,00/82,00 mmHg dan pada kelompok kontrol adalah 167,33/93,33 mmHg. Ada pengaruh pemberian jus semangka terhadap penurunan tekanan darah pada lansia penderita hipertensi di wilayah kerja Puskesmas Lubuk Buaya Padang Tahun 2017Dapat disimpulkan bahwa ada pengaruh pemberian jus semangka terhadap penurunan tekanan darah pada lansia penderita hipertensi. Diharapkan kepada perawat di Puskesmas Lubuk Buaya Padang untuk mensosialisasikan tentang manfaat buah semangka untuk menurunkan tekanan darah pada penderita hipertensi.